Characteristics of the opt-out movement: Early evidence for Colorado - Clayton, Grant; Bingham, Andrea J.; Ecks, Gregory B. (Education Policy Analysis Archives, 2019)
Testing and accountability measures have continued to expand since the passage of the No Child Left Behind Act in 2001. In addition to school and district accountability, student test scores increasingly formed the foundation of teacher performance metrics. State participation rates exceeded the 95% minimum prescribed by law despite increasing opposition to many testing requirements. However, the rollout of the Common Core aligned PARCC tests in 2015 marked the start of a backlash against state mandated testing. The movement, commonly called opt-out, encouraged families not to participate in required tests. We use pooled OLS regression on statewide panel data from Colorado schools to examine school-level characteristics in one of the states with the largest declines in test participation. We find the prevalence of opt-out is largest in charter schools, suburban and rural areas, higher performing schools, and schools with a higher proportion of White students.